2007
DOI: 10.2170/physiolsci.rp008806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric Exercise on Joint Stiffness and Muscle Connectin (Titin) Isoform in the Rat Hindlimb

Abstract: Abstract:We investigated the effects of repeated eccentric exercise for rat medial gastrocnemius muscle on ankle joint stiffness and muscle connectin (titin) isoform composition (longer form, α-connectin; shorter form, β-connectin). Male Wistar rats were trained on a custom-made, isokinetic dynamometer (eccentric-exercise group, n = 6; sham-operated group, n = 6). The exercise session consisted of 20 eccentric contractions elicited by submaximal electric stimulations under anesthesia. The contracting muscle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
(48 reference statements)
7
29
1
Order By: Relevance
“…This is in agreement with human studies examining no influence of a 15 week (Kyrolainen et al, 2005) or 8 week (McGuigan et al, 2003) training program including stretch-shortening cycles on titin isoform expression. The findings were additionally confirmed by an eccentric training study (20 days) using rat M. gastrocnemius medialis (Ochi et al, 2007). In contrast, differential expression of titin isoforms was observed in weight-and powerlifters in comparison to untrained non-athletic individuals .…”
Section: Training Induced Residual Force Enhancementmentioning
confidence: 53%
“…This is in agreement with human studies examining no influence of a 15 week (Kyrolainen et al, 2005) or 8 week (McGuigan et al, 2003) training program including stretch-shortening cycles on titin isoform expression. The findings were additionally confirmed by an eccentric training study (20 days) using rat M. gastrocnemius medialis (Ochi et al, 2007). In contrast, differential expression of titin isoforms was observed in weight-and powerlifters in comparison to untrained non-athletic individuals .…”
Section: Training Induced Residual Force Enhancementmentioning
confidence: 53%
“…In the red portion, intramuscular glycogen was depleted in the HFS group, but clear staining was observed after LFS treatment. The HFS protocol in our experiment is essentially the same as that used by previous studies [18, 27, 28], and this condition led to a supramaximal activation of gastrocnemius muscles. On the other hand, we observed that the exerted force and work volume in the LFS group was about less than 50% of that in the HFS group.…”
Section: Discussionmentioning
confidence: 99%
“…However, since collagen cross-link content did not increase in the Achilles tendons of trained rats, tendon stiffness would not be expected to change even with an increase in collagen content. Interestingly, however, evidence of a decrease in joint stiffness was observed in male rats trained with lengthening contractions over a 20-day period [33].…”
Section: Discussionmentioning
confidence: 99%